The Influence of Financial Literacy, Return, and Risk on The Decision to Invest in Syariah Mutual Funds Using The Bibit Application - Hamdan, Hamdan; Ansharullah, Ansharullah; Faqih El Wafa (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
The increasing development of technology provides convenience in the business world, including investing in sharia mutual funds, so that it can be an alternative choice for students in investing in sharia mutual funds. The purpose of this study is to determine the effect of financial literacy, return and risk partially and simultaneously on the decision of UIN Antasari Banjarmasin students to invest in sharia mutual funds using the bibit application. The research carried out was a type of research with a sample of 100 people based on the Cochran formula. The data collected using. The instruments were analyzed with validity and reliability tests. The data analysis technique used in this study was multiple linear regression. The results of the study show that the variables of financial literacy, return and risk have a positive effect on the decision to invest in Islamic mutual funds according to the hypothesis test where the value obtained by F count (53.371) this value is greater than F table (2.14), so that H0 is accepted, and the level of significance for financial literacy, return and risk is 0.001 <0.1 then H0 is accepted, thus, it can be concluded, financial literacy return and risk have a significant effect on the decision to invest in Islamic mutual funds.